Neuromuscular Electrical Stimulation for Dysphonia and Dysarthria: A Systematic Review (Principles and Practice of Clinical Research, 2023)
Introduction: People with speech disorders such as dysarthria and dysphonia have difficulty produc-ing speech, which is often related to speech muscle dysfunction. Neuromuscular electrical stimulation (NMES) can activate motor units and improve their tropism and functionality. Therefore, this systematic review aimed to evaluate the effects of NMES on the phonation, voice quality, intelligibility, speech muscle strength, and quality of life of patients with dysarthria and dysphonia.Methods: This systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. In September 2022, we searched the EMBASE, Pub-Med, and Cochrane databases for studies that evaluated the effect of NMES on dysarthria and dys-phonia. Randomized controlled trials, observational studies, case series, and case reports were included in the search strategy. The risk of bias in each study was assessed using the ROBINS-I tool.Results: This review included four studies designed as case studies or non-randomized trials with a low risk of bias. NMES showed a positive effect on voice quality and phonation in patients with dysarthria and/or dysphonia. Reported improvements included restored function of the muscles responsible for laryngeal elevation, a reduction in voice breathiness and strain, and enhanced articulation.Discussion: NMES seems to be a promising tool for the rehabilitation of patients with speech disorders. Randomized clinical trials should be conducted to confirm these benefits.Keywords: Neuromuscular stimulation; peripheral electrical stimulation; NMES; electrical stimulation; dysarthria; voice disorders; articulation disorders; dysphonia; phonation disorder; voice disturbance